Etching-free patterning method for electrical characterization of atomically thin MoSe2 films grown by chemical vapor deposition - Utama, Muhammad Iqbal Bakti (2015)
Patterning two-dimensional materials into specific spatial arrangements and geometries is essential for both fundamental studies of materials and practical applications in electronics. However, the currently available patterning methods generally require etching steps that rely on complicated and expensive procedures. We report here a facile patterning method for atomically thin MoSe2 films using stripping with an SU-8 negative resist layer exposed to electron beam lithography. Additional steps of chemical and physical etching were not necessary in this SU-8 patterning method. The SU-8 patterning was used to define a ribbon channel from a field effect transistor of MoSe2 film, which was grown by chemical vapor deposition. The narrowing of the conduction channel area with SU-8 patterning was crucial in suppressing the leakage current within the device, thereby allowing a more accurate interpretation of the electrical characterization results from the sample. An electrical transport study, enabled by the SU-8 patterning, showed a variable range hopping behavior at high temperatures.